Comparison of Antibacterial Mode of Action of Silver Ions and Silver Nanoformulations With Different Physico-Chemical Properties: Experimental and Computational Studies - Kędziora, Anna; Wieczorek, Robert; Speruda, Mateusz; Matolínová, Iva; Goszczyński, Tomasz M.; Litwin, Ireneusz; Matolín, Vladimír; Bugla-Płoskońska, Gabriela (Frontiers in Microbiology, 2021)
The aim of this study was to compare the antibacterial mode of action of silver ions (Ag+) and selected silver nanoformulations against E. coli strains (E. coli J53, Escherichia coli BW25113 and its derivatives: ∆ ompA, ∆ ompC, ∆ ompF, ∆ ompR, ompRG596AcusSG1130A, cusSG1130A). In this research we used various experimental methods and techniques such as determination of the minimal inhibitory concentration, flow cytometry, scanning electron microscopy, circular dichroism as well as computational methods of theoretical chemistry. Thanks to the processing of bacteria and silver samples (ions and nanoformulations), we were able to determine the bacterial sensitivity to silver samples, detect reactive oxygen species (ROS) in the bacterial cells, visualize the interaction of silver samples with the bacterial cells, and identify their interactions with proteins. Differences between the mode of action of silver ions and nanoformulations and the action of nanoformulations themselves were revealed. Based on the results of computational methods, we proposed an explanation of the differences in silver-outer protein interaction between silver ions and metallic silver; in general, the Ag0 complexes exhibit weaker interaction than Ag+ ones. Moreover, we identified two gutter-like areas of the inner layer of the ion channel: one more effective, with oxygen-rich side chains; and another one less effective, with nitrogen-rich side chains.